2017
DOI: 10.3390/vetsci4010015
|View full text |Cite
|
Sign up to set email alerts
|

The Awareness of the International Veterinary Profession of Evidence-Based Veterinary Medicine and Preferred Methods of Training

Abstract: Evidence-based veterinary medicine (EVM) is an evolving discipline in veterinary medicine so it is important to periodically “benchmark” opinion about EVM across the profession. An international survey to assess veterinarians’ awareness of EVM was conducted. Veterinarians were surveyed via an online questionnaire (all countries) or a postal questionnaire (UK only). Participants were asked whether they had heard of EVM, where they had first heard the term, and their preferences of method for receiving continuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…For example, it is possible that particular conditions are more topical, more frequently funded, or more likely to be researched in certain years, leading to over- or under-representation of certain types of conditions for the years examined. Only one database was searched; however, the choice of database was based on previous research, suggesting that CAB Abstracts gives the best coverage of the veterinary literature [ 14 ] and the existence of the veterinary subset function within CAB Abstracts. Additionally, non-English papers were excluded during the searches due to translation time constraints, and it is possible that studies focused on the common conditions affecting rabbits and guinea pigs were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is possible that particular conditions are more topical, more frequently funded, or more likely to be researched in certain years, leading to over- or under-representation of certain types of conditions for the years examined. Only one database was searched; however, the choice of database was based on previous research, suggesting that CAB Abstracts gives the best coverage of the veterinary literature [ 14 ] and the existence of the veterinary subset function within CAB Abstracts. Additionally, non-English papers were excluded during the searches due to translation time constraints, and it is possible that studies focused on the common conditions affecting rabbits and guinea pigs were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Two literature searches, one for each species, were conducted in CAB Abstracts 1910 to 2014 using the OVID interface in November 2014. This database was used as previous research has suggested it provides the best coverage of veterinary journals [ 14 ] and in addition, contains a subset of veterinary citations, allowing searching of these citations specifically. The searches were structured to include only species subject headings (not free text terms), disease/veterinary medicine subject headings and were confined to the veterinary subset (ve.ss).…”
Section: Methodsmentioning
confidence: 99%
“…Our findings indicated that the level of engagement in EBVM across the profession has been variable with motivated practitioners keen to upskill. Historically, the inclusion of EBVM teaching in undergraduate curricula had been limited and whilst recent research shows that awareness is improving, there is a need for more insight into the wider profession's understanding of EBVM and how barriers to its practice can be overcome (Huntley et al, 2017). A future project being undertaken by the team, 'EBVM III', aims to further investigate the profession's challenges to inform the development of an additional practitioner-focused resource.…”
Section: Updating 'Ebvm Learning'mentioning
confidence: 99%
“…Patients and owners also have access to some of this information. As a result, there has been growing pressure from the public, professional bodies, practitioners and students to ensure all professions, including veterinary medicine, continue to be science-driven and evidence-based (Dean et al, 2017;Huntley et al, 2017; and RCVS Code of Professional Conduct for Veterinary Surgeons, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the era of evidence-based veterinary medicine [34], CPGs are becoming an integral part of many aspects of small animal practice. CPGs regarding cardiology [35], dermatology [36], oncology [37], nephrology [38], and antimicrobial treatment [39] have been implemented (see paragraph 3).…”
Section: Introductionmentioning
confidence: 99%